Remote Cerebellar Haemorrhage: A Potential Iatrogenic Complication of Spinal Surgery - Muhammad Atif Naveed (Case Reports in Neurological Medicine, 2018)
We report the case of a 51-year-old man with no significant past medical history, who underwent elective revision spinal surgery and subsequently developed intracranial hypotension, remote cerebellar haemorrhage (RCH), and mild hydrocephalus on the fourth postoperative day. Remote cerebellar haemorrhage is a known complication of supratentorial surgery. This iatrogenic phenomenon may also occur following spinal surgery, due to dural tearing and rapid cerebral spinal fluid (CSF) leakage, resulting in intracranial hypotension and cerebellar haemorrhage. This complication may result in severe permanent neurologic sequelae; hence, it is of pertinence to diagnose and manage it rapidly in order to optimise patient outcome.